Pengaruh Literasi Keuangan, Stress Keuangan, dan Toleransi Risiko terhadap Kepuasan Keuangan Generasi Milenial di Jakarta Pengguna Dompet Digital - Amalia, Agung Dharmawan Buchdadi, Destria Kurnianti (Islamic Education Journal, 2023)
The purpose of this study is to empirically test the effect of financial literacy, financial stressors, and risk tolerance for the financial satisfaction of the millennial generation in Jakarta using digital wallets. The data analysis method in this study uses Partial Least Square - Structural Equation. This study used a sample of 130 respondents. The data collection technique in this study used a questionnaire distributed to the millennial generation in Jakarta. The results of this study indicate that there is a positive and significant relationship between financial literacy and financial satisfaction, then there is a positive and insignificant relationship between financial stress and financial satisfaction, and then there is a positive and insignificant relationship between risk tolerance and financial satisfaction at millennial generation in Jakarta digital wallet users.